2019
DOI: 10.3390/brainsci9120361
|View full text |Cite
|
Sign up to set email alerts
|

Role of MyD88 in IL-1β and Ethanol Modulation of GABAergic Transmission in the Central Amygdala

Abstract: Myeloid differentiation primary response protein (MyD88) is a critical neuroimmune adaptor protein in TLR (Toll-like receptor) and IL-1R (Interleukin-1 receptor) signaling complexes. These two pro-inflammatory families play an important role in the neurobiology of alcohol use disorder, specifically MyD88 regulates ethanol drinking, ethanol-induced sedation, and ethanol-induced deficits in motor coordination. In this study, we examined the role of MyD88 in mediating the effects of IL-1β and ethanol on GABAergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…In support, IL-1 has been found to enhance the hyperpolarizing chloride [172,173] and potassium currents [94] and inhibit the depolarizing sodium [174][175][176] and calcium currents [173,[176][177][178][179]. In addition, IL-1 has been shown to reduce the release of the excitatory neurotransmitter glutamate [163,178,180] and enhance the release and signaling of the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) [172,173,[181][182][183]. These findings are consistent with studies that show IL-1 can reduce excitatory postsynaptic potentials [169].…”
Section: Il-1 and Neuronal Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…In support, IL-1 has been found to enhance the hyperpolarizing chloride [172,173] and potassium currents [94] and inhibit the depolarizing sodium [174][175][176] and calcium currents [173,[176][177][178][179]. In addition, IL-1 has been shown to reduce the release of the excitatory neurotransmitter glutamate [163,178,180] and enhance the release and signaling of the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) [172,173,[181][182][183]. These findings are consistent with studies that show IL-1 can reduce excitatory postsynaptic potentials [169].…”
Section: Il-1 and Neuronal Cell Deathmentioning
confidence: 99%
“…Secondly, the pres-685 ence or absence of non-neuronal IL-1R1 signaling 686 could confound the interpretation of IL-1-mediated 687 changes in neuronal excitability. For example, IL-1 688 induced hyperpolarization of dorsal motor neurons 689was found to be dependent on prostaglandin syn-690 thesis[171] and hyperpolarization of hypothalamic[170] or amygdala neurons[181] was shown to be dependent on MyD88 signaling. These signaling cas-cades are typically observed downstream of IL-1R1 activation in non-neuronal cells such as endothelia and astrocytes, suggesting non-neuronal cells near the recorded neurons could be the main driver of the observed IL-1 effects in these studies.…”
mentioning
confidence: 99%
“…Myeloid differentiation factor 88 (MyD88) mainly mediates the inflammatory response to cell injury as an adaptor protein binding to the Toll-like receptor (TLR) and interleukin 1 receptor (IL-1R). [12][13][14] Previous studies have shown that the abnormal expression of MyD88 is closely related to tumor development and drug resistance. MyD88 is abnormally highly expressed in many kinds of malignant tumor cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…76,77 MYD88 plays a crucial role in signal transduction in the TLR4 signaling pathway and it was reported that the TLR4/MyD88 signaling pathway plays an important role in neuroinflammation. 78,79 IL-1β and IL-6 are typical multifunctional cytokines involved immune responses and inflammation. 80 IL-1β has a wide range of effects and may mediate inflammation or be directly involved in the inflammatory process.…”
mentioning
confidence: 99%